Macrophage Tim-4 protects against deep vein thrombosis by binding CK2β to suppress inflammatory responses - Wang, Xiao; Zhang, Zhen; Zheng, Weiwei; Zhang, Baohui; Chu, Chu; Chen, Junjie; Liu, Cui; Xu, Ke; Yu, Zhijun; Guo, Qiang; Zhao, Songbo; Chen, Xu; et al. (Frontiers in Immunology, 2025)
BackgroundDeep vein thrombosis (DVT) is a venous reflux disorder caused by dysregulated coagulation, with macrophage inflammatory responses being critical for its progression. T-cell immunoglobulin and mucin domain containing 4 (Tim-4) is known as a key regulator of macrophage function and inflammation. However, its involvement in DVT remains completely unclear.MethodsTim-4 expression was comprehensively assessed in peripheral blood mononuclear cells from DVT patients and inferior vena cava-associated macrophages in both clinical specimens and murine DVT models using integrated approaches including single-cell RNA sequencing, immunofluorescence, flow cytometry, quantitative PCR, and Western blot. Macrophage-specific Tim-4 knockout mice (LysM-Cre; Tim-4fl/fl) and littermate controls (Tim-4fl/fl) were constructed to investigate the role of macrophage Tim-4 in DVT. The interaction between Tim-4 and CK2β was verified by mass spectrometry and co-immunoprecipitation. The lncRNF219-3:1/miR-93-5p/Tim-4 regulatory axis was validated through RNA pull-down, RNA antisense purification, and luciferase reporter assays.ResultsTim-4 was significantly downregulated in DVT-associated macrophages, correlating with elevated proinflammatory cytokine levels. Macrophage-specific Tim-4 knockout aggravated DVT progression both in vitro and in vivo. Mechanistically, Tim-4 directly bound casein kinase 2β (CK2β) regulatory subunit, suppressing CK2 holoenzyme activity and subsequent NF-κB pathway activation (pP65 and pIκBα). Notably, pharmacologically blocking CK2 activation or the NF-κB pathway abolished the pro-thrombotic effects of Tim-4 deficiency. Furthermore, we identified a novel ceRNA network wherein lncRNF219-3:1 acted as a miR-93-5p sponge to indirectly upregulate Tim-4 expression, thereby enhancing anti-inflammatory macrophage responses and attenuating thrombus formation.ConclusionsOur findings demonstrate that macrophage Tim-4, regulated by lncRNF219-3:1/miR-93-5p axis, functions as a critical suppressor of DVT through hijacking and sequestering CK2β to dampen NF-κB mediated inflammation. The study unveils novel immunomodulatory mechanisms in DVT pathogenesis and highlights Tim-4 and its regulatory network as potential therapeutic targets for DVT in clinic.